Boredom at the border of philosophy: conceptual and ethical issues - Levine, Peter (Frontiers in Sociology, 2023)
Boredom is a topic in philosophy. Philosophers have offered close descriptions of the experience of boredom that should inform measurement and analysis of empirical results. Notable historical authors include Seneca, Martin Heidegger, and Theodor Adorno; current philosophers have also contributed to the literature. Philosophical accounts differ in significant ways, because each theory of boredom is embedded in a broader understanding of institutions, ethics, and social justice. Empirical research and interventions to combat boredom should be conscious of those frameworks. Philosophy can also inform responses to normative questions, such as whether and when boredom is bad and whether the solution to boredom should involve changing the institutions that are perceived as boring, the ways that these institutions present themselves, or individuals' attitudes and choices.